A modified technique for levator resection in congenital ptosis. Issue 4 (September 2013) - Krohn-Hansen, Dag; Haaskjold, Erling
Abstract This study describes a modified technique for levator resection in congenital ptosis and presents the results from a consecutive series of patients operated on with this method. Eighteen patients were operated on for congenital ptosis. By means of a blunt dissection through the potential space between the levator aponeurosis and the orbital septum, this operation method takes advantage of this anatomical entrance route to surgery on the levator complex, and thereby avoids violation of the orbital septum and the retroseptal fat pad. In a consecutive series of 18 patients with congenital ptosis, 88% of the patients achieved a good result according to the success criteria. In surgery for moderate congenital ptosis, the amount of levator resection is of utmost importance to obtain the desired height of the eyelid. With this method this can be obtained without violating the orbital septum.